Long-Term Outcomes following Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Peritoneal Carcinomatosis of Colorectal Origin - Kadhim Taqi; Jay Lee; Scott Hurton; Cecily Stockley; Lloyd Mack; Justin Rivard; Walley Temple; Antoine Bouchard-Fortier (Current Oncology, 2024)
Background: Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is a major treatment of colorectal peritoneal carcinomatosis (CPC). The aim was to determine the disease-free survival (DFS) and overall survival (OS) of patients undergoing CRS–HIPEC for CPC and factors associated with long-term survival (LTS). Methods: consecutive CPC patients who underwent CRS–HIPEC at a HIPEC center between 2007 and 2021 were included. Actual survival was calculated, and Cox proportional hazards models were used to identify factors associated with OS, DFS and LTS. Results: there were 125 patients with CPC who underwent primary CRS–HIPEC, with mean age of 54.5 years. Median follow-up was 31 months. Average intraoperative PCI was 11, and complete cytoreduction (CC-0) was achieved in 96.8%. Median OS was 41.6 months (6–196). The 2-year and 5-year OS were 68% and 24.8%, respectively, and the 2-year DFS was 28.8%. Factors associated with worse OS included pre-HIPEC systemic therapy, synchronous extraperitoneal metastasis, and PCI ≥ 20 (p < 0.05). Progression prior to CRS–HIPEC was associated with worse DFS (p < 0.05). Lower PCI, fewer complications, lower recurrence and longer DFS were associated with LTS (p < 0.05). Conclusion: CRS and HIPEC improve OS in CPC patients but they have high disease recurrence. Outcomes depend on preoperative therapy response, extraperitoneal metastasis, and peritoneal disease burden.